Pulmonary effects of inhalation of spark-generated silver nanoparticles in Brown-Norway and Sprague–Dawley rats. Issue 1 (December 2016) - Seiffert, Joanna; Buckley, Alison; Leo, Bey; Martin, Nicholas; Zhu, Jie; Dai, Ranran; Hussain, Farhana; Guo, Chang; Warren, James; Hodgson, Alan; Gong, Jicheng; Ryan, Mary; et al.
Abstract Background The increasing use of silver nanoparticles (AgNPs) in consumer products is concerning. We examined the potential toxic effects when inhaled in Brown-Norway (BN) rats with a pre-inflammatory state compared to Sprague–Dawley (SD) rats. Methods We determined the effect of AgNPs generated from a spark generator (mass concentration: 600–800 μg/mm3 ; mean diameter: 13–16 nm; total lung doses: 8 [Low] and 26–28 [High] μg) inhaled by the nasal route in both rat strains. Rats were sacrificed at day 1 and day 7 after exposure and measurement of lung function. Results In both strains, there was an increase in neutrophils in bronchoalveolar lavage (BAL) fluid at 24 h at the high dose, with concomitant eosinophilia in BN rats. While BAL inflammatory cells were mostly normalised by Day 7, lung inflammation scores remained increased although not the tissue eosinophil scores. Total protein levels were elevated at both lung doses in both strains. There was an increase in BAL IL-1β, KC, IL-17, CCL2 and CCL3 levels in both strains at Day 1, mostly at high dose. Phospholipid levels were increased at the high dose in SD rats at Day 1 and 7, while in BN rats, this was only seen at Day 1; surfactant protein D levels decreased at day 7 at the high dose in SD rats, but was increased at Day 1 at the low dose in BN rats. There was a transient increase in central airway resistance and in tissue elastance in BN rats at Day 1 but not in SD rats. Positive silver-staining was seen particularly in lung tissue macrophages in a dose and time-dependent response in both strains, maximal by day 7. Lung silver levels were relatively higher in BN rat and present at day 7 in both strains. Conclusions Presence of cellular inflammation and increasing silver-positive macrophages in lungs at day 7, associated with significant levels of lung silver indicate that lung toxicity is persistent even with the absence of airway luminal inflammation at that time-point. The higher levels and persistence of lung silver in BN rats may be due to the pre-existing inflammatory state of the lungs.